Effect of dietary supplementation with omega-3 and -6 on fresh and frozen/thawed sperm quality of dogs - Rodrigues, Ana Carolina; Ruiz, Camila Montanari; De Nardo, Carla Daniela Dan; Mothé, Gabriele Barros; Rossi, Fabiano Martinez; De Sousa, Daniel Bartoli; Netto, Halim Atique; De Souza, Fabiana Ferreira [UNESP] (Universidade Estadual de Londrina, 2017)
For years, fatty acids have been recommended as a dietary supplement to improve canine hair. For animal reproduction, supplementation with omegas has been used to increase the reproductive efficiency and conception rate, but few studies have been conducted in dogs. The aim of this study was to evaluate the effects of daily dietary supplementation with omega-3 and -6 on the quality of fresh and frozen/thawed semen in canines. Semen was collected from seven dogs and evaluated for sperm motility, vigor, concentration, and morphology. The 17-week study included 119 ejaculates and was divided according to oral supplementation with omega-3 and -6: M1 (1st-5th week) or pre-supplementation; M2 (6th-9th week) and M3 (10th-13th week) or during supplementation; and M4 (14th-17th week) or post-supplementation. After analysis, the semen was frozen and then revaluated both immediately and 30 minutes (at 37° C) after thawing. Supplementation with omegas increased sperm motility, vigor, and concentration; however, supplementation had no influence on semen freezability. In addition, there was no improvement in sperm motility after supplementation when the thawed cells were maintained at 37° C for 30 minutes. We concluded that dietary supplementation with omega-3 and -6 for 4 to 8 weeks can improve the quality of fresh semen, although it has no effect on the freezability of canine semen.
Keywords: Canine; Diet-supplemented; Polyunsaturated-fatty-acid; Sperm